Genetic Predisposition To Acquire a Polybasic Cleavage Site for Highly Pathogenic Avian Influenza Virus Hemagglutinin - Naganori Nao (American Society for Microbiology, 2017)
ABSTRACT Highly pathogenic avian influenza viruses with H5 and H7 hemagglutinin (HA) subtypes evolve from low-pathogenic precursors through the acquisition of multiple basic amino acid residues at the HA cleavage site. Although this mechanism has been observed to occur naturally only in these HA subtypes, little is known about the genetic basis for the acquisition of the polybasic HA cleavage site. Here we show that consecutive adenine residues and a stem-loop structure, which are frequently found in the viral RNA region encoding amino acids around the cleavage site of low-pathogenic H5 and H7 viruses isolated from waterfowl reservoirs, are important for nucleotide insertions into this RNA region. A reporter assay to detect nontemplated nucleotide insertions and deep-sequencing analysis of viral RNAs revealed that an increased number of adenine residues and enlarged stem-loop structure in the RNA region accelerated the multiple adenine and/or guanine insertions required to create codons for basic amino acids. Interestingly, nucleotide insertions associated with the HA cleavage site motif were not observed principally in the viral RNA of other subtypes tested (H1, H2, H3, and H4). Our findings suggest that the RNA editing-like activity is the key mechanism for nucleotide insertions, providing a clue as to why the acquisition of the polybasic HA cleavage site is restricted to the particular HA subtypes. IMPORTANCE Influenza A viruses are divided into subtypes based on the antigenicity of the viral surface glycoproteins hemagglutinin (HA) and neuraminidase. Of the 16 HA subtypes (H1 to -16) maintained in waterfowl reservoirs of influenza A viruses, H5 and H7 viruses often become highly pathogenic through the acquisition of multiple basic amino acid residues at the HA cleavage site. Although this mechanism has been known since the 1980s, the genetic basis for nucleotide insertions has remained unclear. This study shows the potential role of the viral RNA secondary structure for nucleotide insertions and demonstrates a key mechanism explaining why the acquisition of the polybasic HA cleavage site is restricted to particular HA subtypes in nature. Our findings will contribute to better understanding of the ecology of influenza A viruses and will also be useful for the development of genetically modified vaccines against H5 and H7 influenza A viruses with increased stability.